THE PATTERNS OF DISTRIBUTION AND HABITAT CHARACTERISTICS OF Acanthopleura gemmata IN THE LITORAL ZONE OF LHOKNGA BEACH, ACEH BESAR DISTRICT - Wardana, Siti; S, M. Ali; Saputri, Mimie; Fajriana, Nurul (Jurnal Biologi Sains dan Kependidikan, 2022)
This study aims to determine the pattern of distribution of Acanthopleura gemmata and the characteristics of the habitat of Acanthopleura gemmata, in Lhoknga Coastal Waters, Aceh Besar District. The research method is observation. The research area was divided into 4 locations namely I Cemara Beach, location II Pasi Jalang Beach, location III Simet Beach and location IV Ujong Lhoknga Beach, Aceh Besar District. Sampling was carried out along the Litoral Zone. Parameters in this study are biological parameters and physico-chemical parameters. Data analysis used the Morishita Index and Principal Component Analysis (PCA). The physico-chemical environmental factors at Lhoknga Beach are water temperature (28C-38C), sediment temperature (28C-38C) pH (6.81-6.95?7), and salinity (25o/oo-26o/oo). The results showed that the Simet Beach Morishita Index was 1.05 ?1, Ujung Beach was 1.01 ?1, while Cemara Beach and Pasi Jalang Beach did not have Acanthopleura gemmata. Habitat characteristics of Acanthopleura gemmata are found in coral rocks, moss and sand substrates. The conclusion of this study is the distribution pattern of Acanthopleura gemmata in the littoral zone of Lhoknga Beach which is random, the habitat characteristics of Acanthopleura gemmata are coral reefs, moss and sand sediments, while the distribution pattern has a positive relationship with the physical-chemical environmental factors of Acanthopleura gemmata which includes pH, except for salinity, water temperature and sediment temperature.Key words: distribution patterns, habitat characteristics, Lhoknga Beach